Impact of Substrate-Based Ablation for Ventricular Tachycardia in Patients with Frequent Appropriate Implantable Cardioverter-Defibrillator Therapy and Dilated Cardiomyopathy: Long-Term Experience with High-Density Mapping - Oliveira, MM (2021)
Introduction: Recurrent ventricular tachycardia (VT) episodes have a negative impact on the clinical outcome of implantable cardioverter-defibrillator (ICD) patients. Modification of the arrhythmogenic substrate has been used as a promising approach for treating recurrent VTs. However, there are limited data on long-term follow-up. Aim: To analyze long-term results of VT substrate-based ablation using high-density mapping in patients with severe left ventricular (LV) dysfunction and recurrent appropriate ICD therapy. Methods: We analyzed 20 patients (15 men, 55% with non-ischemic cardiomyopathy, age 58±15 years, LV ejection fraction 32±5%) and repeated appropriate shocks or arrhythmic storm (>2 shocks/24 h) despite antiarrhythmic drug therapy and optimal heart failure medication. All patients underwent ventricular programmed stimulation (600 ms/S3) to document VT. A sinus rhythm (SR) voltage map was created with a three-dimensional electroanatomic mapping system (CARTO, Biosense Webster, CA) using a PentaRay® high-density mapping catheter (Biosense Webster, CA) to delineate areas of scarred myocardium (ventricular bipolar voltage ≤0.5 mV --- dense scar; 0.5-1.5 mV --- border zone; ≥1.5 mV --- healthy tissue) and to provide high-resolution electrophysiological mapping. Substrate modification included elimination of local abnormal ventricular activities (LAVAs) during SR (fractionated, split, low-amplitude/long-lasting, late potentials, pre-systolic), and linear ablation to obtain scar homogenization and dechanneling. Pace-mapping techniques were used when capture was possible. The LV approach was retrograde in nine cases, transseptal in five and epi-endocardial in four. In two patients ablation was performed inside the right ventricle. Results: LAVAs and scar areas were modified in all patients. Mean procedure duration was 149 min (105-220 min), with radiofrequency ranging from 18 to 70 min (mean 33 min) and mean fluoroscopy time of 15 min. Non-inducibility was achieved in 75% of cases (in four patients with hemodynamic deterioration and an LV assist device, VT inducibility was not performed). There were two cases of pericardial tamponade, drained successfully. During a follow-up of 50±24 months, 65% had no VT recurrences. Among the seven patients with recurrences, three underwent redo ablation and four, with fewer VT episodes, received appropriate ICD therapy. There were five hospital readmissions due to heart failure decompensation, one patient died in the first week after unsuccessful ablation of a VT storm and three died (stroke and pneumonia) >1 year after ablation. Conclusion: Catheter ablation based on substrate modification is feasible and safe in patients with frequent VTs and severe LV dysfunction. This approach may be of clinical relevance, with potential long-term benefits in reducing VT burden.